High-temperature lead-free piezoelectric ceramic material and preparation method thereof
Through the A/B-position composite doping strategy, the lattice distortion and oxygen vacancy distribution of Bi4Ti3O12 ceramics are adjusted, which solves the problem of low piezoelectric performance of lead-free piezoelectric ceramic materials at high temperatures, and achieves the combination of high-voltage electrical performance and stability at high temperatures.
Patent Information
- Application Number
- CN202411885112.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Existing lead-free piezoelectric ceramic materials have low piezoelectric performance at high temperatures, and the Curie temperature is difficult to maintain, which cannot meet the needs of high-temperature applications.
The A/B position composite doping strategy is adopted to dopate the A position by doping the A position by introducing inequivalent co-doping of high- and low-priced metal cations at the B position, and adjusting the lattice distortion and oxygen vacancy distribution of Bi4Ti3O12 ceramics.
While maintaining high Curie temperature, it significantly improves the piezoelectric properties of ceramics, enhances the stability and resistivity of the material, and is suitable for high-temperature piezoelectric applications.
Smart Images

Figure CN119683995A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of piezoelectric ceramics, and in particular relates to a high-temperature lead-free piezoelectric ceramic material and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics are an important type of functional material. They can realize the mutual conversion between mechanical vibration and electrical signals by using the forward and reverse piezoelectric effects. They are now widely used in sensors, filters, transformers, ultrasonic imaging and other fields. With the rapid development of science and technology in the fields of aerospace and nuclear power from the 1960s to the 1990s, the demand for high-temperature applications has gradually increased. Lead zirconate titanate piezoelectric ceramics (PZT) cannot achieve safe monitoring under high temperatures. Therefore, researchers are committed to developing lead-free piezoelectric ceramic materials with high Curie temperature, environmental friendliness and high performance to replace lead-based piezoelectric materials. Among the many lead-free piezoelectric materials, bismuth layer structured ceramics (BLSFs) have a high Curie temperature (T C >600℃), low aging rate, high dielectric breakdown strength and high mechanical quality factor (Q m ) and other advantages, making it the preferred material for key piezoelectric components in high-temperature piezoelectric vibration sensors.
[0003] BLSFs ceramics, whose general chemical formula is (Bi 2 O 2 ) 2+ (A m-1 B m O 3m+1 ) 2- , is given by (Bi 2 O 2 ) 2+ Layer and (A m- 1 B m O 3m+1 ) 2- A ceramic with a specific structure formed by alternating layers along the c axis. A is usually a twelve-coordinated monovalent, divalent or trivalent cation and its composite ion, such as Na + , Ba 2+ 、Bi 3+ etc., B is a tetravalent, pentavalent or hexavalent cation or its composite ion suitable for octahedral coordination, such as Ti 4+ 、 5+ , W 6+etc., where m is the number of perovskite-like layers, generally an integer from 1 to 5. However, this special layered structure makes the piezoelectric properties of this type of piezoelectric ceramic material affected by orientation, resulting in low piezoelectric activity. In addition, during the sintering process, the Bi element in the structure is prone to volatilization, leading to an increase in the carrier concentration, which also affects the electrical properties of the material.
[0004] Currently, in this field, B-site or A / B-site composite doping modification is usually adopted to improve the piezoelectric properties of bismuth-layered structure high-temperature piezoelectric ceramics. For example, it can be achieved by co-doping with Cr 3+ , Ta 5+ to prepare bismuth-layered structure Bi 4 Ti 3 O 12 piezoelectric ceramics, whose piezoelectric coefficient has been increased to 26 pC / N. It is also possible to prepare Bi 3.96 Ce 0.04 Ti 2.97 W 0.015 Nb 0.015 O 12 ceramics through the A / B-site composite doping strategy, increasing the piezoelectric coefficient of bismuth-layered high-temperature piezoelectric ceramics to more than 34 pC / N, but the Curie temperature decreases. The properties of piezoelectric ceramics often affect each other. The higher the piezoelectric coefficient, the lower the Curie temperature usually is. How to improve the piezoelectric properties of the material while maintaining its relatively high Curie temperature is an urgent problem to be solved. Summary of the Invention
[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a high-temperature lead-free piezoelectric ceramic material, which can improve the piezoelectric properties of the material while maintaining a relatively high Curie temperature.
[0006] The present invention also provides a preparation method for the high-temperature lead-free piezoelectric ceramic material.
[0007] In the first aspect of the present invention, a high-temperature lead-free piezoelectric ceramic material is provided, with a chemical composition of Bi 4-x A x Ti 2.97 (B1 1 / 3 B2 2 / 3 ) 0.03 O 12 , where 0 < x < 0.08. Among them, A is a doping element of a metal cation with a radius close to Bi 3+ , B1 is a doping element of a low-valence metal cation, B2 is a doping element of a high-valence metal cation, and B1 and B2 form an unequal valence doping of high-valence and low-valence metal cations.
[0008] One technical solution in the technical solution of the present invention regarding the high-temperature lead-free piezoelectric ceramic material has at least the following beneficial effects:
[0009] The present invention provides a bismuth layered high temperature piezoelectric ceramic material, which uses A / B position composite doping to replace Bi 4 Ti 3 O 12 The method of using bismuth ions at position A and titanium ions at position B is to use a near Bi 3+ The radius metal cation element is used for doping at the A position, and the B1 element and B2 element are used for unequal doping at the B position to introduce Bi 3+ Bi with similar ionic radius 3+ The radius metal cation, combined with the B-site unequal co-doping strategy of high-valent ions and low-valent ions, effectively reduced the oxygen vacancy concentration and was also able to adjust the Bi 4 Ti 3 O 12 The degree of lattice distortion of the oxygen octahedron in the bismuth layered structure enables it to achieve the effect of improving the piezoelectric performance while maintaining a high Curie temperature.
[0010] According to some embodiments of the invention, 0.02≤x≤0.06.
[0011] According to some embodiments of the present invention, the near Bi 3+ Radius metal cations include Ce 3+ and La 3+ One of the high-valent metal cations includes Ta 5+ , Nb 5+ and Sb 5+ One of the low-valent metal cations B1 includes Cr 3+ , Mn 3+ and Mg 2+ One of them.
[0012] According to some embodiments of the present invention, when the near Bi 3+ The radius metal cation is Ce 3+ , the high-valent metal cation is Ta 5+ , the low-valent metal cation B1 is Cr 3+ When the chemical composition is Bi 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12 (BiCTCT-100x).
[0013] For Bi 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 )0.03 O 12 Ceramics, the A-position Ce element exists in the form of Ce 3+ , the B-site composite doping ion combination is The existence forms of Cr and Ta are Cr 3+ and Ta 5+ .
[0014] From the structural point of view, the Curie temperature T of bismuth layered piezoelectric ceramics c Related to the tolerance factor t:
[0015]
[0016] where r A 、r B 、r O Represent the radius of the A-site cation, B-site cation and oxygen ion respectively. Generally speaking, the smaller t is, the larger T C The higher. and replace After that, the t value becomes smaller, so that T C At the same time, generally speaking, the influence of A-position doping on t value is greater, so it is chosen to introduce Ionic radii similar After replacement, the t value remains relatively unchanged.
[0017] When Ta 5+ and Cr 3+ Replace Ti 4+ The oxygen vacancy concentration can be reduced by:
[0018]
[0019] According to the charge compensation principle, Ta is introduced 2 O 5 and Cr 2 O 3 Later, 5+ and Cr 3+ Ion substitution of Ti in BIT 4+ Ions can produce and Cr′ Ti defect. Therefore, (Cr 1 / 3 / Ta 2 / 3 ) donor doping can effectively reduce the oxygen vacancy concentration, which is one of the main reasons for the increase in the resistivity of BiCTCT-100x ceramics.
[0020] At the same time, Ce at position A 3+ ions then replace the Bi in BIT 3+ Ions, produced defects, and to some extent inhibited the Bi 3+ The volatilization of Ce ions. This process reduces the concentration of oxygen vacancies. Therefore, the donor doping of Ce ions effectively reduces the number of oxygen vacancies, which is also one of the main reasons for the increase in resistivity of BiCTCT-100x ceramics.
[0021] Experiments have shown that adjusting the concentration of A-site ions by combining B-site unequal co-doping is an effective strategy to improve the electrical properties of BIT-based ceramics. It can significantly improve the piezoelectric properties while maintaining a high Curie temperature, and maintain a high Curie temperature and excellent temperature stability at high temperatures.
[0022] The second aspect of the present invention provides a method for preparing the high temperature lead-free piezoelectric ceramic material of the first aspect of the present invention, comprising the following steps:
[0023] S1: Weigh Bi according to the stoichiometric ratio 2 O 3 、TiO 2 , an oxide of element A, an oxide of element B1 and an oxide of element B2, mixing them and wet-milling them, and drying the milled slurry to obtain a powder;
[0024] S2: pre-calcining the powder to obtain pre-calcined powder, and granulating and tableting part of the pre-calcined powder to obtain a green body;
[0025] S3: after debinding the green body, using part of the pre-burned powder to bury the green body with powder and then solid phase sintering to obtain a ceramic sheet;
[0026] S4: After printing the electrode material on the surface of the ceramic sheet, polarization treatment is performed to obtain the high-temperature lead-free piezoelectric ceramic material.
[0027] A technical solution in the method for preparing high-temperature lead-free piezoelectric ceramic material of the present invention has at least the following beneficial effects:
[0028] 1. Improved high temperature stability and piezoelectric performance: By adopting near Bi 3+ The doping of the A-site with the radius metal cation and the unequal co-doping of the B1 and B2 elements at the B-site effectively adjusted the Bi 4 Ti 3 O 12 The lattice distortion in the bismuth layered structure reduces the concentration of oxygen vacancies and improves the stability and piezoelectric properties of the material.
[0029] 2. Enhanced Curie temperature: Through the unequal doping strategy, a high Curie temperature (i.e., the ability of the material to maintain a strong piezoelectric effect at high temperatures) is maintained, so that the material exhibits excellent piezoelectric properties in high-temperature environments and meets the needs of high-temperature applications.
[0030] 3. Lead-free and environmentally friendly: The use of lead-free bismuth layered piezoelectric ceramic materials meets environmental protection requirements and avoids the potential harm of traditional lead-based piezoelectric materials to the environment and human body.
[0031] 4. Controllable ceramic preparation process: Through wet ball milling, pre-sintering, granulation, tableting, sintering and other steps, the microstructure and phase composition of ceramic materials can be precisely controlled to ensure high performance and uniformity of the materials.
[0032] 5. Simple and efficient preparation process: The entire preparation process is relatively simple and efficient, capable of mass-producing high-performance, high-temperature, lead-free piezoelectric ceramic materials, and has certain industrialization potential.
[0033] In step S1:
[0034] Bi 2 O 3 、TiO 2 , oxide of element A, oxide of element B1 and oxide of element B2, with a purity of 99.9%.
[0035] Considering that Bi is volatile at high temperatures, 2 O 3 Excess 1wt%-5wt%, preferably, Bi 2 O 3 Excess 3wt%.
[0036] After mixing, wet ball milling is performed, and the ball-milled slurry is dried to obtain a powder;
[0037] The ball mill is a polytetrafluoroethylene ball mill with zirconium oxide grinding balls, and the mass ratio of ingredients to grinding balls is 1:2-4.
[0038] There are three sizes of grinding balls: large, medium and small, and the mass ratio can be 3:4:3.
[0039] According to some embodiments of the present invention, the oxide of element A comprises CeO 2 ,La 2 O 3 One of them.
[0040] According to some embodiments of the present invention, the oxide of element B1 includes Cr 2 O 3 , MgO, the oxide of element B2 includes Ta 2 O 5 , Nb 2 O 5 One of them.
[0041] According to some embodiments of the present invention, the rotation speed of the wet ball milling is 300 rpm to 400 rpm.
[0042] According to some embodiments of the present invention, the rotation speed of the wet ball milling is any value of 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm, 400rpm or a range formed by any two of them, such as 340rpm to 360rpm.
[0043] According to some embodiments of the present invention, the wet ball milling time is 4 hours to 12 hours.
[0044] According to some embodiments of the present invention, the wet ball milling time is any one of 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range formed by any two of them, such as 6h to 10h.
[0045] According to some embodiments of the present invention, the ball-milled slurry is dried at 80° C. to 90° C. for 1 h to 2 h, and then sieved (through a 60-mesh sieve).
[0046] In step S2:
[0047] According to some embodiments of the present invention, the pre-firing temperature is 750°C to 850°C.
[0048] According to some embodiments of the present invention, the pre-firing temperature can be any value of 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C or a range formed by any two of them, such as 800°C to 830°C.
[0049] According to some embodiments of the present invention, the pre-burning time is 2 hours to 4 hours.
[0050] According to some embodiments of the present invention, the pre-burning time is any one of 2h, 2.5h, 3h, 3.5h, 4h, or a range formed by any two of them, such as 2.5h to 3.5h.
[0051] Pre-calcination allows the chemical reaction between the raw materials to proceed fully and synthesize the required phases, while removing impurities in the raw materials and improving density.
[0052] Preferably, the pre-firing condition is 850° C. for 2 hours.
[0053] The calcined powder is reserved for buried powder sintering during the sintering process, one is to reduce the volatilization of Bi during the sintering process, and the other is to prevent the ceramic sheets from sticking.
[0054] Using pre-burned powder for granulation and tableting can effectively improve the density of the sample, reduce the porosity, and thus increase the resistivity of the sample.
[0055] In the present invention, the binder that can be used is an alcohol solution of polyvinyl butyral (PVB), 4%-6% PVB solution is added and fully ground until the alcohol evaporates, and then the granulated powder is sieved (through a 60-mesh sieve). The granulated powder can be weighed 0.40g each time, poured into a circular tableting mold with a diameter of 10mm, and maintained at a pressure of 5-10MPa for 10-60s, and pressed to obtain a disc; then cold isostatic pressing is performed, the pressure is 200MPa, and the holding time is 10-30min.
[0056] In step S3:
[0057] The green body is subjected to a debinding treatment to remove the binder added during granulation, and can be kept at 350°C for 1 hour and then heated to 500°C for 1 hour.
[0058] According to some embodiments of the present invention, the temperature of the solid phase sintering is 1080°C to 1120°C.
[0059] According to some embodiments of the present invention, the holding time of the solid phase sintering is 2 h to 3 h.
[0060] According to some embodiments of the present invention, in order to improve the quality of the sintered sheets, the temperature rising process of the solid phase sintering is staged heating, rising to 850°C~950°C at 2°C / min~3°C / min, and then rising to the sintering temperature at 3°C / min~5°C / min for heat preservation.
[0061] In step S4:
[0062] After printing the electrode material on the surface of the ceramic sheet and before performing the polarization treatment, the sintered ceramic disc is firstly polished, and then silver paste is printed on both sides, and then the ceramic disc is cured at 720° C. for 15 minutes.
[0063] According to some embodiments of the present invention, the temperature of the polarization treatment is 160°C to 200°C.
[0064] According to some embodiments of the present invention, the polarization electric field of the polarization treatment is 6 kV / mm to 8 kV / mm.
[0065] According to some embodiments of the present invention, the polarization time of the polarization treatment is 20 min to 30 min.
[0066] According to some embodiments of the present invention, the polarization is performed by heating in an oil bath.
[0067] After polarization, the piezoelectric and other performance tests can be performed on the prepared high-temperature lead-free piezoelectric ceramic material.
[0068] The third aspect of the present invention provides a piezoelectric device, comprising the high-temperature lead-free piezoelectric ceramic material of the first aspect of the present invention or the high-temperature lead-free piezoelectric ceramic material prepared by the method of the second aspect of the present invention.
[0069] One of the technical solutions of the present invention regarding the piezoelectric device has at least the following beneficial effects:
[0070] 1. High temperature stability: The piezoelectric device using the high temperature lead-free piezoelectric ceramic material of the first aspect of the present invention or the material prepared by the method of the second aspect can still maintain good piezoelectric performance in a high temperature environment and is suitable for high temperature applications such as automotive electronics, industrial sensors and other fields.
[0071] 2. Lead-free and environmentally friendly: The piezoelectric device uses lead-free piezoelectric ceramic materials, which meets environmental protection requirements, avoids the harmful effects of traditional lead-based piezoelectric materials, complies with the increasingly stringent global environmental standards, and is suitable for use in regions and markets with stricter environmental regulations.
[0072] 3. High voltage electrical performance: through close Bi 3+ The doping of radius metal cations and unequal co-doping at the B position significantly improve the piezoelectric performance of the material of the present invention, can provide stronger electrical response capability, enhance the efficiency of piezoelectric devices, and is widely applicable to high-precision piezoelectric applications such as sensors, drivers, and sonar systems.
[0073] 4. Optimized crystal structure: Since the crystal structure of the material of the present invention is optimized through a specific doping strategy during the preparation process, the oxygen vacancy concentration is reduced and the lattice distortion of the oxygen octahedron is adjusted, the piezoelectric device has better stability and reliability and can maintain excellent performance during long-term use.
[0074] 5. Broad application prospects: This piezoelectric device is suitable for a variety of industrial and consumer electronics fields, especially in situations where high-temperature piezoelectric performance is required, such as high-temperature sensors, energy collection devices, acoustic wave sensors, etc., to meet the growing technical needs of high efficiency, environmental protection and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 The high temperature lead-free piezoelectric ceramic material Bi of the present invention 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12 Preparation flow chart of .
[0076] Figure 2 The piezoelectric coefficient test results of BiCTCT-100x samples after annealing at various temperatures.
[0077] Figure 3 The performance of the ceramic of the present invention is comparable to that of other Bi-based 4 Ti 3 O 12 Comparison results of ceramic doping and modification products. DETAILED DESCRIPTION
[0078] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0079] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0080] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0081] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0082] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0083] In the embodiment of the present invention, Bi 4-x A x Ti 2.97 (B1 1 / 3 B2 2 / 3 ) 0.03 O 12 Abbreviated as BiCTCT-100x.
[0084] Example
[0085] A high-temperature lead-free piezoelectric ceramic material Bi was prepared 4-x Ce xTi 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12 , where x = 0, 0.02, 0.04, 0.06, 0.08.
[0086] Preparation process Figure 1 As shown, the specific process is:
[0087] Weigh Bi according to the stoichiometric ratio 2 O 3 (99.9%), CeO 2 (99.9%), TiO 2 (99%), Cr 2 O 3 (99.99%), Ta 2 O 5 (99.99%) powder, considering that Bi is volatile at high temperature, 2 O 3 Excess 3wt%.
[0088] Pour the prepared raw materials into a polytetrafluoroethylene ball mill, add zirconium oxide grinding balls at the same time, the ratio of the raw materials to the grinding balls is 1:3, the mass ratio of the large, medium and small grinding balls is 3:4:3, and then add an appropriate amount of anhydrous ethanol to basically cover the grinding balls, and finally cover the lid for wet ball milling. The ball milling condition is 350r / min, and the ball milling time is 6h. The slurry after ball milling is dried at 85℃ for 1h, and then sieved (through a 60-mesh sieve).
[0089] Pour the powder into an alumina crucible for pre-sintering at a temperature of 800°C for 3 hours. Pre-sintering allows the chemical reaction between the raw materials to fully proceed, synthesizing the desired phase, while removing impurities in the raw materials and improving density. The preferred pre-sintering condition is 850°C for 2 hours. The calcined powder is reserved for buried powder sintering during the sintering process, firstly to reduce the volatilization of Bi during the sintering process, and secondly to prevent the ceramic sheets from sticking.
[0090] Using the pre-burned powder for granulation and tableting can effectively improve the density of the sample, reduce the porosity, and thus improve the resistivity of the sample. The binder used in this embodiment is an alcohol solution of polyvinyl butyral (PVB), 5% PVB solution is added and fully ground until the alcohol evaporates, and then the granulated powder is sieved (through a 60-mesh sieve). Weigh 0.40g of the granulated powder each time, pour it into a circular tableting mold with a diameter of 10mm, hold the pressure at 5-10MPa for 10-60s, and pressurize to obtain a disc; then perform cold isostatic pressing, the pressure is 200MPa, and the holding time is 10-30min.
[0091] The green body is subjected to a debinding treatment to remove the binder added during granulation, that is, it is kept at 350°C for 1 hour and then heated to 500°C for 1 hour.
[0092] The sample after debinding was buried with pre-burned powder, and then solid phase sintering was performed, with a sintering temperature of 1000°C, a holding time of 2h, and a heating rate of 3°C / min. In particular, in order to improve the quality of the sintered sheet, a staged heating method was adopted, with the temperature rising to 900°C at 2°C / min, and then rising to the sintering temperature at 4°C / min for holding.
[0093] The sintered ceramic disc was ground and polished, and then silver paste was printed on both sides, and then high-temperature curing was carried out by keeping the temperature at 720°C for 15 minutes.
[0094] The sample was polarized by oil bath heating, the polarization temperature was 180°C, the polarization electric field was 7 kV / mm, and the polarization time was 25 min.
[0095] The piezoelectric and other properties of the polarized ceramic sheets are tested.
[0096] The present invention is at position B On the basis of unequal doping, the introduction of Ce ions with the same valence as Bi ions at the A position can effectively reduce the impact on the Curie temperature. BiCTCT-100x ceramics are prepared by solid phase sintering, and the ceramic resistivity is improved by reducing the volatilization of Bi and the concentration of oxygen vacancies, so that Bi is increased while maintaining its high Curie temperature. 4 Ti 3 O 12 Piezoelectric properties and stability of base ceramics.
[0097] Table 1 shows Bi with different doping levels x 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12 Performance parameters of ceramics.
[0098] Table 1
[0099]
[0100] From Table 1, we can see that A / B co-doping can improve Bi 4 Ti 3 O 12 Comprehensive electrical properties of base ceramics (pure Bi prepared by traditional methods 4 Ti 3 O 12The piezoelectric coefficient of ceramics is about 3.5pC / N). When x=0.04, the piezoelectric coefficient of BiCTCT-100x ceramics is the largest, which is 37pC / N. The piezoelectric performance is better than that of pure Bi 4 Ti 3 O 12 At the same time, at 500°C, it has the lowest dielectric loss (tanδ=0.078) and a higher resistivity, which can reach 6.6×10 6 Ω·cm, relative to pure Bi 4 Ti 3 O 12 For ceramics, the high temperature resistivity is increased by two orders of magnitude (pure Bi prepared by traditional solid phase sintering 4 Ti 3 O 12 The high temperature resistivity of ceramics is about 10 4 Ω·cm).
[0101] Ce 3+ Substitution causes lattice distortion and regulates the distribution of oxygen vacancies, thereby improving the piezoelectric performance. In addition, the Curie temperature of BiCTCT-4 ceramics is higher than that of pure Bi. 4 Ti 3 O 12 Ceramic(T C =675℃). When B and replace After that, the t value becomes smaller, so that T C Increase.
[0102] At the same time, unlike other technologies where Ce ions have a +4 valence, which would cause greater lattice distortion, in the present invention, due to the synergistic effect of unequal doping at the B position, Ce ions at the A position only have a +3 valence. and The ionic radius of Ce is similar, so the t value remains relatively unchanged after substitution. However, with the increase of Ce content, the orthorhombicity of the crystal decreases, resulting in T C Therefore, on the basis of unequal doping at the B site, Ce ions with a radius similar to that of Bi ions are introduced at the A site, which effectively minimizes the effect on T C The influence of C value.
[0103] Figure 2 is the piezoelectric coefficient of the BiCTCT-100x sample after annealing at various temperatures. It can be seen that the piezoelectric performance of the sample is relatively stable and can still maintain a relatively high piezoelectric coefficient after annealing at 500°C. c After annealing at 2000 °C, the ceramic undergoes a transformation from ferroelectric phase to paraelectric phase.33 Almost 0.
[0104] The piezoelectric properties and Curie temperature of the present invention are compared with other Bi-based 4 Ti 3 O 12 The results of the invention work on ceramic doping and modification are compared. Figure 3 shown. Figure 3 middle, Figure 3 In, W / Nb refers to Bi 4 Ti 2.9 W 0.05 Nb 0.05 O 12 ;
[0105] W / Cr refers to Bi 4 Ti 2.95 W 0.05 O 12.05 +0.2wt.%Cr 2 O 3 ;
[0106] Ce / W / Nb refers to Bi 3.96 Ce 0.04 Ti 2.97 W 0.015 Nb 0.015 O 12 ;
[0107] Mg / Nb refers to Bi 4 Ti 2.95 (Mg 1 / 3 Nb 2 / 3 ) 0.05 O 12 ;
[0108] Ce / W / Ta refers to Bi 3.96 Ce 0.04 Ti 2.94 W 0.03 Ta 0.03 O 12 ;
[0109] W / Mn refers to Bi 4 Ti 2.9 W 0.1 O 12 +4wt.%Mn 2 O 3 ;
[0110] W / Ta refers to Bi 4 Ti 2.92 W 0.04 Ta 0.04 O 12 ;
[0111] Mn / Nb refers to Bi 4 Ti 2.95 (Mn 1 / 3 Nb 2 / 3 ) 0.05 O 12 ;
[0112] Zn / Nb refers to Bi 4 Ti 2.93 (Zn 1 / 3 Nb 2 / 3 ) 0.07 O 12 ;
[0113] Nb / Ta refers to Bi 4 Ti 2.98 Nb 0.01 Ta 0.01 O 12 ;
[0114] Cu / Sb refers to Bi 4 Ti 2.965 (Cu 1 / 3 Sb 2 / 3 ) 0.035 O 12 ;
[0115] Cu / Nb refers to Bi 4 Ti 2.95 (Cu 1 / 3 Nb 2 / 3 ) 0.05 O 12 .
[0116] It can be found that other work 4 Ti 3 O 12 While improving the piezoelectric performance of the ceramic sample, the Curie temperature also dropped significantly, both lower than that of pure Bi. 4 Ti 3 O 12 The Curie temperature of ceramics is 675°C, while the BiCTCT-4 sample in the present invention can maintain an excellent Curie temperature (681°C) while obtaining excellent piezoelectric properties (37pC / N). This result confirms that the modification of the A-site equivalent ion based on the B-site inequivalent doping is an effective way to improve the Bi 4 Ti 3 O 12 The modification strategy of the comprehensive electrical properties of ceramics will provide some reference directions for the subsequent modification of piezoelectric ceramics.
[0117] Comparative Example
[0118] Usually, Ce ions are doped into the A position and exist in a mixed state of +3 and +4 valence, but this will lead to aggravated lattice distortion and a significant decrease in Curie temperature. However, under the synergistic effect of unequal doping at the B position, Ce ions in the ceramic sample only exist in a single valence state of +3 valence, which effectively reduces the effect of doping at the A position on the Curie temperature. Table 2 shows the Bi ions of the high temperature lead-free piezoelectric ceramic material of the present invention. 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12 (x=0.04, abbreviated as Ce / Cr / Ta) Comparative example with other works.
[0119] Table 2
[0120]
[0121] In Table 2, Ce / W / Ta represents Bi 3.96 Ce 0.04 Ti 2.94 W 0.03 Ta 0.03 O 12 ;Ce / W / Nb represents Bi 3.96 Ce 0.04 Ti 2.9 7 W 0.015 Nb 0.015 O 12 .
[0122] The present invention proposes a modification strategy of introducing the same-valence A-site atom for doping based on the unequal-valence doping at the B-site. 4 Ti 3 O 12 , using cerium, chromium and tantalum elements for doping. In particular, generally speaking, the addition of mixed Ce ions of +3 and +4 valence into the A position will cause a significant decrease in the Curie temperature. However, due to the synergistic effect of the B-position unequal doping strategy in the present invention, the A-position Ce ion can be obtained as a single positive trivalent Ce ion, which can effectively reduce the impact on the Curie temperature. At the same time, this strategy can effectively reduce the oxygen vacancy concentration, and its B-position composite unequal doping ion combination is That is, the composition is Bi 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12, by inducing lattice distortion and regulating the distribution of oxygen vacancies, the effect of improving piezoelectric performance is achieved, which is within the scope of protection of the present invention.
[0123] Considering the volatilization of Bi, the raw material has an excess of Bi, preferably 3% excess Bi. Pre-burned powder is used for granulation and tableting. Pre-burning can effectively remove impurities in the powder and generate BIT powder. In addition, pre-burned powder is also used for buried powder sintering to reduce the volatilization of Bi during the sintering process and prevent the adhesion of ceramic sheets. Then the sample is prepared by solid phase sintering, and the sintering quality of the sample is improved by staged heating. For this experimental scheme, the preferred sintering process is 1120℃-2h, and the heating rate is 3℃ / min, wherein the temperature is first increased to 900℃ at 2℃ / min, and then increased to the sintering temperature at 3℃ / min, which is within the scope of protection of this patent.
[0124] From the experimental results, through the A-Ce and B- Composite substitution, the piezoelectric properties of the ceramics are improved. At the same time, with the increase of the A-site doping amount, the Curie temperature is generally between 671 and 682 °C, which is close to that of pure Bi. 4 Ti 3 O 12 The Curie temperature of ceramics (T C =675°C). Therefore, the use of ions with similar ionic radius at the A site combined with the unequal doping strategy at the B site can effectively improve the piezoelectric performance while reducing the impact on the Curie temperature, while achieving high resistivity at high temperatures and excellent temperature stability.
[0125] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A high temperature lead-free piezoelectric ceramic material, characterized in that: The chemical composition is Bi 4-x A x Ti 2.97 (B1 1 / 3 B2 2 / 3 ) 0.03 O 12 , 0 < x < 0.08, where A is a doping element of a near-Bi 3+ radius metal cation, B1 is a doping element of a low-valence metal cation, B2 is a doping element of a high-valence metal cation, and B1 and B2 form a non-equivalent doping of high-valence and low-valence metal cations.
2. The high temperature lead-free piezoelectric ceramic material according to claim 1, characterized in that: The near Bi 3+ Radius metal cations include Ce 3+ and La 3+ One of the high-valent metal cations includes Ta 5+ , Nb 5+ and Sb 5+ One of the low-valent metal cations includes Cr 3+ , Mn 3+ and Mg 2+ One of them.
3. The high temperature lead-free piezoelectric ceramic material according to claim 1, characterized in that: When the near Bi 3+ The radius metal cation is Ce 3+ , the high-valent metal cation is Ta 5+ , the low-valent metal cation is Cr 3+ When the chemical composition is Bi 4-x Ce x Ti 2.97 (Cr 1 / 3 Ta 2 / 3 ) 0.03 O 12 .
4. A method for preparing a high temperature lead-free piezoelectric ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Bi2O3, TiO2, oxide of element A, oxide of element B1 and oxide of element B2 are weighed according to the stoichiometric ratio, mixed and wet-milled, and the milled slurry is dried to obtain a powder; S2: pre-calcining the powder to obtain pre-calcined powder, and granulating and tableting part of the pre-calcined powder to obtain a green body; S3: after debinding the green body, using part of the pre-burned powder to bury the green body with powder and then solid phase sintering to obtain a ceramic sheet; S4: After printing the electrode material on the surface of the ceramic sheet, polarization treatment is performed to obtain the high-temperature lead-free piezoelectric ceramic material.
5. The method according to claim 4, characterized in that The oxide of element A includes one of CeO2 and La2O3; optionally, the oxide of element B1 includes one of Cr2O3 and MgO, and the oxide of element B2 includes one of Ta2O5 and Nb2O5.
6. The method according to claim 4, characterized in that The solvent of the wet ball milling includes ethanol; optionally, the rotation speed of the wet ball milling is 300 rpm to 400 rpm; optionally, the time of the wet ball milling is 4 h to 12 h.
7. The method according to claim 4, characterized in that The pre-firing temperature is 750° C. to 850° C.; optionally, the pre-firing time is 2 h to 4 h.
8. The method according to claim 4, characterized in that The temperature of the solid phase sintering is 1080°C to 1120°C; optionally, the insulation time of the solid phase sintering is 2h to 3h; optionally, the heating process of the solid phase sintering is staged heating, heating to 850°C to 950°C at 2°C / min to 3°C / min, and then heating to the sintering temperature at 3°C / min to 5°C / min for insulation.
9. The method according to claim 4, characterized in that The temperature of the polarization treatment is 160° C. to 200° C.; optionally, the polarization electric field of the polarization treatment is 6 kV / mm to 8 kV / mm; optionally, the polarization time of the polarization treatment is 20 min to 30 min.
10. A piezoelectric device, characterized in that: The invention comprises the high-temperature lead-free piezoelectric ceramic material according to any one of claims 1 to 3 or the high-temperature lead-free piezoelectric ceramic material prepared by the method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Multielement-doped bismuth titanate group lead-free piezoceramic material and preparation method thereof
CN102167585A
Layered perovskite multiferroic material and preparation method thereof
CN103224392A
Bismuth layered piezoelectric ceramic material as well as preparation method and application thereof
CN117303890A
Process for the preparation of bismuth sodium titanate
WO2020152483A1
Cited By
Piezoelectric ceramic for high-temperature vortex shedding flowmeter and preparation method thereof
CN120965315A
Sb < 3 + > / Ta < 5 + > co-doped bismuth titanate-based piezoelectric ceramic as well as preparation method and application thereof
CN121085633A